PROFIL KEMAMPUAN ATLET AEROBIC GYMNASTIC RIAU DIMASA PANDEMI COVID 19 DALAM MENGKONSUMSI VOLUME OKSIGEN SECARA MAKSIMAL - Muhammad Imran; Agus Sulastio; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstrack: The problem in this research is that after the made observations in the field, the researchers would give the athletes a test in the form of bleeps, the results of which were that the endurance of all athletes was very poor because during training and competitive, good vo2max proficiency was needed. The aim of this research was to determine the ability of the Riau Aerobic Gymnastics athletes during the Covid-19 pandemic to consume the maximum volume of oxygen. The population in this research were Riau Gymnastics athletes, a total of 7 samples using a total sampling technique. The instrument in this research is the bleep test. The results of this research during the covid-19 pandemic there was a decrease in vo2max endurance against all aerobic gymnastic Riau athletes from the vo2max level before the covid-19 pandemic era with 4 samples in the excellent category, then 2 very good categories and 1 example good category. while during the covid-19 pandemic, data was obtained in the very good category, there were 3 people, then there were 2 people in the good category, and one athlete was in the fair category. Key Words: Vo2max Endurance Consuming Power Profile, Gymnastics Riau.